Three-Dimensional Measurements of Pharynx Structures in Malocclusion (Medico Legal Update, 2019)
Background/Objectives: The present study was conducted to examine differences between malocclusion the pharynx by reconstructing 3D images from CBCT data using the Mimics program, which allows actual measurement values to be acquired that are not affected by image distortion.Method/Statistical Analysis: The subjects were analyzed by dividing them into malocclusion of classes I, II, and III (with each group comprising five participants) according to their facial skeletal forms. DICOM images were 3-dimensional ones manufactured by using the 3-D image program(Mimics 17, Materialise, Leuven, Gelgium). Upper airways in subjects of class I,II and III were divided into rhinopharynx, oropharynx and laryngopharynx.Findings: The volume of the nasopharynx was 11521.9600 for class I, 11925.5850 for class II, and 13167.2800 for class III; the corresponding values for the oropharynx were 10946.0500, 8547.6125, and 12126.3125, respectively, indicating no significant differences. The volume ratio of the nasopharynx was 51.0534 for class I, 58.1387 for class II, and 51.9762 for class III; the corresponding values for the oropharynx were 48.9466, 41.8613, and 48.0238, respectively, also indicating no significant differencesImprovements/Applications: However, the present 3D measurements based on data measured in two dimensions are expected to facilitate future studies and provide basic data for them.